HISTORICAL ROOTS OF NATIONAL VALUES - Hamdam Umarov (American Journals, 2025)
The article highlights the historical roots of national and religious values, their role in society and human life. It is analyzed that national and universal values existed in interdependence, and that universal values, such as honesty, tolerance and justice, developed on the basis of national customs and traditions.
Keywords: National and universal values, customs, traditions, honesty, tolerance, humanity, hospitality, good neighborliness, historical heritage.